Faktor Psikologi dan Sosial dalam Membentuk Minat Beli Produk Taste Twist di Jatinangor - Darpito, Dhanesworo; Muttaqin, Zaenal (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to analyze the influence of stress, taste preferences, and social factors on consumer purchasing decisions for healthy food products, focusing on Taste Twist products in Jatinangor. The method used is a qualitative approach through semi-structured interviews with purposively selected respondents. The results of the study indicate that stress levels affect food preferences, where individuals tend to choose foods that provide emotional comfort. Preferences for local flavors, such as rendang and gulai, also play an important role in influencing consumer purchasing interest, especially those who have an emotional attachment to traditional flavors. Social factors, such as recommendations from friends and family, also influence purchasing decisions, especially in the context of trying new products. In conclusion, consumer purchasing decisions for healthy food products are influenced by a combination of stress, taste preferences, and social influences. Therefore, the development of healthy food products such as Taste Twist needs to balance between delicious taste and health benefits in order to attract more consumers.